Glucose versus fructose metabolism in the liver measured with deuterium metabolic imaging - Hendriks, Arjan D.; Veltien, Andor; Voogt, Ingmar J.; Heerschap, Arend; Scheenen, Tom W. J.; Prompers, Jeanine J. (Frontiers in Physiology, 2023)
Chronic intake of high amounts of fructose has been linked to the development of metabolic disorders, which has been attributed to the almost complete clearance of fructose by the liver. However, direct measurement of hepatic fructose uptake is complicated by the fact that the portal vein is difficult to access. Here we present a new, non-invasive method to measure hepatic fructose uptake and metabolism with the use of deuterium metabolic imaging (DMI) upon administration of [6,6'-2H2]fructose. Using both [6,6'-2H2]glucose and [6,6'-2H2]fructose, we determined differences in the uptake and metabolism of glucose and fructose in the mouse liver with dynamic DMI. The deuterated compounds were administered either by fast intravenous (IV) bolus injection or by slow IV infusion. Directly after IV bolus injection of [6,6'-2H2]fructose, a more than two-fold higher initial uptake and subsequent 2.5-fold faster decay of fructose was observed in the mouse liver as compared to that of glucose after bolus injection of [6,6'-2H2]glucose. In contrast, after slow IV infusion of fructose, the 2H fructose/glucose signal maximum in liver spectra was lower compared to the 2H glucose signal maximum after slow infusion of glucose. With both bolus injection and slow infusion protocols, deuterium labeling of water was faster with fructose than with glucose. These observations are in line with a higher extraction and faster turnover of fructose in the liver, as compared with glucose. DMI with [6,6'-2H2]glucose and [6,6'-2H2]fructose could potentially contribute to a better understanding of healthy human liver metabolism and aberrations in metabolic diseases.